RANCANG BANGUN APLIKASI SISTEM PELAYANAN PADA RUMAH MAKAN BERBASIS CLIENT SERVER (Studi Kasus Depot Pak ‘D’ Ketintang Surabaya) - Suhendi, Laizim; Kadek Dwi Nuryana, I (Inovate, 2016)
It is inevitable that during the development of this technology has brought enormous impact on variousaspects, one aspect of the business world. Application system promises ease, efficiency, speed, andaccuracy of the data processed either in small, medium and large scale.Service system at home or a restaurant meal that can be processed by an application system not only interms of ease and speed up the manual data processing to be accurate and structured, but it can bedeveloped into a system of application service to consumers.The purpose of the application system in home care client server-based diet is destined for employeesand business people the culinary field in order to provide optimal service to consumers. In addition,system service application on the client-server-based restaurant is expected to bring a positive impact onbusinesses in the competitive world of technology applied in the business world, so that the positivebenefits to be obtained. Keyword: Application systems, client server, website, business, restaurant